2013
DOI: 10.1111/jvh.12201
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early treatment discontinuation in a cohort of patients treated with boceprevir‐based therapy for hepatitis C infection

Abstract: In this real-world cohort, 49% of patients stopped boceprevir-based hepatitis C therapy early, with only 20% stopping due to treatment futility. Having more comorbidities was significantly associated with early discontinuation. Tolerability of boceprevir-based regimens may be substantially worse than reported in clinical trials, particularly for patients with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
3
9
0
1
Order By: Relevance
“…However, this study found that female patients were at an increased risk for therapy noncompletion, and the higher percentage of females in this study relative to studies of the VA population may partially explain the higher discontinuation rate found in this study. [14][15][16][17] Taken holistically, the results from the current study support evidence in the literature that completion rates of DAA therapy regimens in the real-world are lower than in clinical trials, which report 66%-73% completion rates in telaprevir patients 10,11 and 60%-65% completion rates in boceprevir patients. 8,9 The higher completion rates found in clinical trials likely reflect the carefully selected patient populations and additional resources used to encourage patient compliance with medications.…”
Section: ■■ Conclusionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, this study found that female patients were at an increased risk for therapy noncompletion, and the higher percentage of females in this study relative to studies of the VA population may partially explain the higher discontinuation rate found in this study. [14][15][16][17] Taken holistically, the results from the current study support evidence in the literature that completion rates of DAA therapy regimens in the real-world are lower than in clinical trials, which report 66%-73% completion rates in telaprevir patients 10,11 and 60%-65% completion rates in boceprevir patients. 8,9 The higher completion rates found in clinical trials likely reflect the carefully selected patient populations and additional resources used to encourage patient compliance with medications.…”
Section: ■■ Conclusionsupporting
confidence: 78%
“…14,15 In another VA database analysis, Ioannou et al (2014) defined duration of treatment from the first fill of PEG/ RBV to the last day of treatment covered by PEG/RBV and found that approximately 41%-45% of telaprevir patients did not complete at least 24 weeks of therapy, and 40%-55% of boceprevir patients did not complete at least 28 weeks of therapy. 17 Finally, Majid et al (2014) found that 49% of boceprevir patients discontinued therapy prior to 24 weeks. 16 The higher rates of therapy noncompletion found in the current study are likely attributable to a stricter definition of therapy completion and differences in the study populations.…”
Section: Resource Utilization and Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] This results in an increased proportion of adverse events, dropouts and hence lower effectiveness. [28] Our results support the ‘development paradox’ and provide reasons why real world outcomes do differ from registration trials.…”
Section: Discussionsupporting
confidence: 59%